MODEL PERENCANAAN PEMBELAJARAN PAI INTEGRATIF BERBASIS KOMPETENSI ABAD KE-21 MENUJU GENERASI EMAS INDONESIA 2045 - Ahwani, Muhamad Alfan; Syahlarriyadi; Sutarto (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2025)
This study seeks to develop a model for integrative Islamic Religious Education (PAI) learning design grounded in 21st-century competencies as a comprehensive strategy to support the realization of Indonesia’s Golden Generation 2045. Employing a library research methodology, the study adopts a content analysis approach that draws upon credible and authoritative literature, including scholarly journals, academic books, and educational policy documents. The findings reveal that existing PAI learning planning models remain predominantly oriented toward cognitive achievement, with limited integration of key 21st-century competencies: critical thinking, creativity, collaboration, and communication (4C). The novelty of this research lies in its formulation of a conceptual framework that synthesizes 21st-century competency principles with the value-based nature of Islamic education, thereby producing a learning design that is both responsive to global dynamics and aligned with the Pancasila Student Profile. Furthermore, this study recommends future empirical investigations, such as experimental or field-based research, to evaluate the model’s practical effectiveness across various educational levels and institutions. Consequently, the proposed model is expected to make a substantive and meaningful contribution to the transformation of PAI learning in advancing Indonesia’s Golden Generation 2045.